Poor health, physical workload and occupational social class as determinants of health-related job loss: results from a prospective cohort study in the UK. Issue 7 (11th July 2019) - Sewdas, Ranu; van der Beek, Allard J; Boot, Cecile R L; D'Angelo, Stefania; Syddall, Holly E; Palmer, Keith T; Walker-Bone, Karen
Abstract : Objectives: The aims of the present study were to assess the association and interactions of physical workload and poor health with health-related job loss (HRJL) among older workers, and the association and interactions of occupational social class and poor health with HRJL. Methods: Data were used from an existing prospective cohort study, Health and Employment after Fifty, where employed or self-employed workers aged 50–64 years (n=4909) were followed-up between 2014 and 2016. Associations between potential determinants (self-perceived health status, physical workload and occupational social class) and 2-year HRJL were examined by Cox regression analyses. To study whether physical workload or occupational social class moderates the influence of poor health on HRJL, additive and multiplicative interactions were calculated. Results: Older workers with poor self-perceived health status had increased risk of HRJL during the 2-year follow-up period (men: HR 2.57 (95%CI: 1.68 to 3.92); women: HR 3.26 (95%CI: 2.33 to 4.55)). Furthermore, men with high physical workload were at increased risk for HRJL (HR 1.63 (95%CI: 1.09 to 2.43)). No significant interactions (p<0.05) were identified between poor health and high physical workload, nor between poor health and lower occupational social class. Conclusion: Our study indicates that older workers in poor health, and older workers with a physically demanding job, are at increased risk of HRJL. Having a physically demanding job or working in routine/manual occupations does not moderate the association between poor health and HRJL.